MEMASUKI PASAR EKSPOR : PERBEDAAN ANTARA EKSPORTIR SISTEMATIK DAN TIDAK SISTEMATIK - Muhammad, Osman (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
This paper discuses the characteristic of malaysian exporters which have ventured into new markets, The comparison is made between systematic and non systematic exporters. The result show that systematic exporters are more likely to be larger in size and they achieved better export performance compared to Â their counterparts. The differences between systematic exporters and non systematics exporters can also traced to their sources of marketings strengths